ANALISIS STRATEGI PEMASARAN PADA HOTEL GRAN PURI MANADO - MANGAHA, CHINDY; KALANGI, JOHNY; TAMENGKEL, LUCKY (Sam Ratulangi University, 2020)
Increasingly competitive competition in the hotel world also triggers competition in offeringevery facility and product available in each hotel in order to increase sales. Gran Puri Manado Hotel usesa marketing mix to support its marketing strategy. This study aims to analyze the marketing strategycarried out by the Gran Puri Manado Hotel in increasing sales. Promotional activities include coupons,discounts, samples and contests. in increasing sales of the Gran Puri Manado Hotel.This research uses a qualitative method, which is a case study that produces descriptive data thatis set forth in words. The interview technique was carried out by conducting a direct visit to conduct apersonal interview with the Gran Puri Manado Hotel and equipped with the data obtained. Which thecompany can develop, maintain, and improve product quality so that people continue to believe in theproducts and facilities provided.Keywords: Marketing Strategy, Marketing Mix, Marketing Services